Pengembangan Metode PJBL Menggunakan Media Interaktif Berbasis (Canva) Untuk Siswa Kelas XII RPL SMKN 2 Padang - Anaperta, Megasyani; Turahma, Wilda; Rahmayani, Elya Putri; Saputra, Firman (Universitas Labuhanbatu, 2023)
This research aims to find out information and data related to the learning process at school, the devices used by schools to support learning activities, the strategies used by teachers during the learning process, student responses to the delivery of learning material from teachers, media and student worksheets at SMKN 2 Padang in the learning process carried out by the teacher in the classroom. The research carried out consisted of two, namely qualitative and quantitative data. Qualitative data was obtained from data from observations and interviews, while quantitative data was obtained from quiz tests on Canva-based interactive media and assessments by filling out questionnaires. The research results showed that the module developed was categorized as very valid with a percentage of 87.94%. Furthermore, based on the practicality data processing, the percentage of module practicality level was 88.03% and it can be concluded that the average practicality of the learning media that has been developed is very practical.